High-adhesion anisotropic electronic skin and preparation method thereof
By preparing high-adhesion anisotropic electronic skin, and using the circulating freeze-thaw method to achieve directional freezing, the existing electronic skin has poor adhesion performance, small temperature range and poor antibacterial performance, and the effects of high adhesion, wide temperature range and strong antibacteriality are achieved.
Patent Information
- Application Number
- CN202411842197.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-25
AI Technical Summary
The existing electronic skin has poor adhesion performance, small temperature range and poor antibacterial properties, which limits its use range.
The preparation method of high adhesion anisotropic electronic skin is adopted, and the electronic skin surface patching agent, PVA, conductive antibacterial agent, water-retaining antifreeze and sodium decahydrate tetraborate are mixed evenly, and prepared by circulating freeze-thawing method to achieve directional freezing and adjust its performance.
It achieves high adhesion performance, wide temperature range of electronic skin, excellent conductivity, good biocompatibility and self-healing ability, as well as strong antibacterial properties, expanding its application range.
Smart Images

Figure HDA0005188210450000011 
Figure HDA0005188210450000012 
Figure HDA0005188210450000013
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing electronic skin, and in particular to a high-adhesion anisotropic electronic skin and a method for preparing the same. Background Art
[0002] As a human-machine interface connecting the human body and the machine, the adhesion performance of the electronic skin directly affects the sensitivity and stability of the monitoring signal. Highly adhesive electronic skin can move with the movement of the skin, perfectly adhere to the skin surface, and achieve dynamic stability of human signal monitoring. However, existing hydrogels have problems such as poor adhesion, a small temperature range of use, and poor antibacterial properties, which seriously limit the scope of use of electronic skin. Therefore, it is of great significance to prepare a highly adhesive and antibacterial electronic skin with a wide range of uses. Summary of the invention
[0003] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a method for preparing high-adhesion anisotropic electronic skin.
[0004] To achieve the purpose, the technical solution adopted by the present invention is:
[0005] A highly adhesive anisotropic electronic skin, wherein the raw materials are composed of the following in terms of mass percentage: 0.5wt% to 3wt% electronic skin surface patch, 8wt% to 25wt% PVA, 1wt% to 3wt% conductive antibacterial agent, 1wt% to 3wt% water-retaining antifreeze agent, 0.3wt% to 1.5wt% sodium tetraborate decahydrate, and the remainder is deionized water. The highly adhesive anisotropic electronic skin is prepared by mixing the raw materials evenly and pouring them into a mold, and then using a freeze-thaw cycle method, which specifically includes the following steps:
[0006] Step 1, adding the electronic skin surface patch to part of the deionized water, and mixing them evenly at 90-100° C. to obtain solution A;
[0007] Step 2, adding PVA to solution A, mixing at 90-100° C. for 1.5-2 h to obtain a uniformly mixed solution B;
[0008] Step 3, adding the antibacterial agent to solution B, and mixing by ultrasonication to obtain solution C;
[0009] Step 4, adding the water-retaining antifreeze agent to solution C, and mixing uniformly by ultrasonication to obtain solution D;
[0010] Step 5, adding sodium tetraborate decahydrate to the remaining deionized water, and mixing them uniformly at 90-100° C. to obtain solution E;
[0011] Step 6, mixing solution D and solution E evenly to obtain solution F;
[0012] Step 7, pouring solution F into a polytetrafluoroethylene mold with a thick copper block as the top cover;
[0013] Step 8, immerse the bottom of the polytetrafluoroethylene mold containing solution F in liquid nitrogen for 20 to 40 minutes (the thick copper block does not contact the liquid nitrogen), and then take it out;
[0014] Step 9, placing the polytetrafluoroethylene mold in a refrigerator at -18 to -16°C and freezing for 5 to 8 hours;
[0015] Step 10, taking the polytetrafluoroethylene mold out of the refrigerator, placing it in a room temperature environment, and thawing it for 10 to 15 hours;
[0016] Step 11, repeat step 9 and step 10 3 to 5 times;
[0017] Step 12, taking the sample out of the mold to obtain a highly adhesive anisotropic electronic skin;
[0018] Step 13: Use an electronic encapsulation agent to fully encapsulate the electronic skin. The bottom of the encapsulation layer is detachable, and the bottom encapsulation layer is uncovered when in use.
[0019] Furthermore, in the solution D, the mass percentage of water is 72% to 85%.
[0020] Furthermore, the electronic skin surface patch is one of chitosan, carrageenan, curdlan gum, sodium alginate and hydroxycellulose.
[0021] Furthermore, the molecular weight of the PVA is 78,000 to 158,000.
[0022] Furthermore, the conductive antibacterial agent is one or both of silver nanowires and silver nanoparticles. Silver nanowires and silver nanoparticles can be used not only as antibacterial agents but also as conductive agents.
[0023] Furthermore, the water-retaining antifreeze agent is one of CaCl2 and polyol.
[0024] Furthermore, the electronic encapsulant is one of Ecoflex00-10, Ecoflex00-20 and Ecoflex00-30.
[0025] Furthermore, the thickness of the encapsulant package is 0.8 to 1.3 mm.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] 1. The present invention uses a directional freezing method to prepare anisotropic electronic skin. The use temperature range, tensile properties, conductive properties, adhesion properties, etc. of the electronic skin can be adjusted by the direction and time of directional freezing to expand its use range. Specifically: The present invention first immerses the bottom of the mold in liquid nitrogen, and uses the low temperature of liquid nitrogen to freeze the sample from the bottom to the top, and then puts the mold into a refrigerator, and uses the thick copper block (thickness of 3 to 5 cm) as the top cover of the mold. The thermal conductivity rate is faster than that of polytetrafluoroethylene, so that the sample is frozen from the top to the bottom, achieving directional freezing of the sample.
[0028] 2. The electronic skin of the present invention has excellent adhesion properties and can be attached to surfaces of various materials. It can also monitor and collect various signals very sensitively and stably.
[0029] 3. The electronic skin of the present invention has excellent load-bearing performance and toughness. When cut into long strips, it can lift 500g of hand sanitizer without breaking.
[0030] 4. The electronic skin of the present invention has good biocompatibility and self-healing ability. Both PVA and chitosan have very good biocompatibility. In application, they can be better attached to the surface of the organism. In addition, boron ions are introduced into the PVA system, and the boron ions form dynamic boron ester bonds with hydroxyl groups, thereby obtaining self-healing ability.
[0031] 5. The electronic skin of the present invention also has very good antibacterial properties, which is a very important property of electronic skin. If the antibacterial properties of the material do not meet the requirements, the material will become moldy and ineffective in a short time. The antibacterial agent used in the electronic skin of the present invention is at least one of silver nanowires and silver nanoparticles. At the same time, silver is also a conductor with excellent electrical conductivity. Without the need to add additional conductive fillers, it can provide good electrical conductivity for the electronic skin. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the cross section of the high-adhesion anisotropic electronic skin prepared in Example 1;
[0033] Figure 2 This is a SEM image of the cross section of the high-adhesion anisotropic electronic skin prepared in Example 1;
[0034] Figure 3 This is a SEM image of the silver nanowires used in Example 1;
[0035] Figure 4 This is a test chart showing that the highly adhesive anisotropic electronic skin prepared in Example 1 withstands the weight of a bottle of hand sanitizer weighing 500 g;
[0036] Figure 5This is a diagram showing the state of the highly adhesive anisotropic electronic skin prepared in Example 1 adhering to the surface of human skin;
[0037] Figure 6 The resistance of the highly adhesive anisotropic electronic skin prepared in Example 1 varies with strain;
[0038] Figure 7 The GF value of the highly adhesive anisotropic electronic skin prepared in Example 1 varies with strain;
[0039] Figure 8 This is a state diagram of the highly adhesive anisotropic electronic skin prepared in Example 1 and Example 2 adhering to the surface of an aluminum sheet;
[0040] Fig. 9 This is a state diagram of the high-adhesion anisotropic electronic skin prepared in Example 1 and Example 2 adhering to the epoxy resin surface. DETAILED DESCRIPTION
[0041] In order to further illustrate the features and advantages of the present invention, embodiments of the present invention are described in detail below. The following embodiments are only a part of the present invention, and the protection scope of the present invention is not limited to the following embodiments.
[0042] Unless otherwise specified, the reagents and materials used in the following examples can be obtained from commercial sources.
[0043] Example 1
[0044] In this embodiment, the highly adhesive anisotropic electronic skin is prepared according to the following steps:
[0045] (1) Add 0.25 g of chitosan to 35 g of deionized water, and stir and mix at 90° C. to obtain solution A.
[0046] (2) Add 8.5 g of PVA (molecular weight 128,000) to solution A and stir at 90°C for 2 h to completely dissolve the PVA to obtain solution B;
[0047] (3) Add 0.5 g of silver nanowires to solution B and mix them evenly by ultrasonic mixing to obtain solution C.
[0048] (4) Add 0.5 g of CaCl2 to solution C and mix thoroughly by ultrasonic mixing to obtain solution D.
[0049] (5) 0.25 g of sodium tetraborate decahydrate was added to 5 g of deionized water, and the mixture was mixed at 90° C. to obtain a mixed solution E.
[0050] (6) Solution D and solution E are mixed evenly to obtain solution F.
[0051] (7) Solution F is poured into a polytetrafluoroethylene mold with a thick copper block as the top cover.
[0052] (8) The bottom of the polytetrafluoroethylene mold containing solution F was immersed in liquid nitrogen for 20 min and then taken out.
[0053] (9) Place the polytetrafluoroethylene mold in a -18°C refrigerator and freeze for 5 hours.
[0054] (10) Take the polytetrafluoroethylene mold out of the refrigerator and place it in a room temperature environment to thaw for 10 hours.
[0055] (11) Repeat steps 9 and 10 three times.
[0056] (12) The sample is taken out of the mold to obtain a highly adhesive anisotropic electronic skin.
[0057] (13) The electronic skin is encapsulated using the electronic encapsulant Ecoflex00-10, and the thickness of the encapsulation is 0.8 mm.
[0058] Figure 1 Schematic diagram of the cross section of the highly adhesive anisotropic electronic skin prepared in Example 1, Figure 2 This is a SEM image of the cross section of the highly adhesive anisotropic electronic skin prepared in Example 1. It can be seen from the image that the holes in the electronic skin matrix are stretched along the Y-axis direction, and the direction of hole stretching is the direction of directional freezing.
[0059] Figure 3 This is the SEM image of the silver nanowires used in Example 1.
[0060] Figure 4 This is a test chart showing that the high-adhesion anisotropic electronic skin prepared in Example 1 withstands the weight of a bottle of hand sanitizer weighing 500g. It can be seen from the chart that this electronic skin has high strength and strong toughness.
[0061] Figure 5 This is a state diagram of the highly adhesive anisotropic electronic skin prepared in Example 1 adhering to the surface of human skin. It can be seen from the figure that the electronic skin can adhere to the surface of human skin very firmly.
[0062] Figure 6 The resistance of the high-adhesion anisotropic electronic skin prepared in Example 1 changes with strain. It can be seen from the figure that the resistance of the electronic skin first decreases and then increases with the increase of strain, and the resistance reaches the minimum when the strain is about 7%.
[0063] Figure 7The GF value of the high-adhesion anisotropic electronic skin prepared in Example 1 changes with strain. It can be seen from the figure that the GF value of the electronic skin first increases and then decreases with the increase of strain. The use range of this electronic skin is within the strain of 5%.
[0064] Example 2
[0065] In this embodiment, the highly adhesive anisotropic electronic skin is prepared according to the following steps:
[0066] (1) 0.5 g of hydroxycellulose was added to 32 g of deionized water and mixed at 100° C. to obtain solution A.
[0067] (2) 10.25 g of PVA (molecular weight 10,500) was added to solution A and stirred at 100° C. for 1.5 h to completely dissolve the PVA, thereby obtaining solution B.
[0068] (3) Add 1 g of silver nanoparticles to solution B and mix them evenly by ultrasonic mixing to obtain solution C.
[0069] (4) Add 0.5 g of polyol (glycerol) to solution C and mix well by ultrasonication to obtain solution D.
[0070] (5) 0.25 g of sodium tetraborate decahydrate was added to 5.5 g of deionized water, and the mixture was mixed at 100° C. to obtain a mixed solution E.
[0071] (6) Solution D and solution E are mixed evenly to obtain solution F.
[0072] (7) Solution F is poured into a polytetrafluoroethylene mold with a thick copper block as the top cover.
[0073] (8) The bottom of the polytetrafluoroethylene mold containing solution F was immersed in liquid nitrogen for 30 min and then taken out.
[0074] (9) Place the polytetrafluoroethylene mold in a -16°C refrigerator and freeze for 5 hours.
[0075] (10) Take the polytetrafluoroethylene mold out of the refrigerator and place it in a room temperature environment to thaw for 10 hours.
[0076] (11) Repeat steps 9 and 10 for a total of 5 times.
[0077] (12) taking the sample out of the mold to obtain a highly adhesive anisotropic electronic skin;
[0078] (13) The electronic skin is encapsulated using the electronic encapsulant Ecoflex00-10, and the thickness of the encapsulation is 1 mm.
[0079] Figure 8 The state diagram of the highly adhesive anisotropic electronic skin prepared in Example 1 (left) and Example 2 (right) adhering to the surface of an aluminum sheet, Fig. 9 The state diagram of the highly adhesive anisotropic electronic skin prepared in Example 1 (left) and Example 2 (right) adhering to the epoxy resin surface. It can be seen from the figure that the samples obtained in Example 1 and Example 2 can be firmly adhered to the surface of the standing aluminum sheet and the epoxy resin sheet, indicating that they can be adhered to the surfaces of different materials.
[0080] Comparative Example 1
[0081] In this embodiment, the electronic skin is prepared according to the following steps:
[0082] (1) 10.25 g of PVA (molecular weight 10500) was added to 32.5 g of deionized water and stirred at 100° C. for 1.5 h to completely dissolve the PVA to obtain solution A.
[0083] (2) Add 1 g of silver nanoparticles to solution A and mix them evenly by ultrasonic mixing to obtain solution B.
[0084] (3) Add 0.5 g of polyol (glycerol) to solution B and mix them evenly by ultrasonication to obtain solution C.
[0085] (4) 0.25 g of sodium tetraborate decahydrate was added to 5.5 g of deionized water, and the mixture was mixed at 100° C. to obtain a mixed solution D.
[0086] (5) Solution C and solution D are mixed evenly to obtain solution E.
[0087] (6) Solution E is poured into a polytetrafluoroethylene mold with a thick copper block as the top cover.
[0088] (7) The bottom of the polytetrafluoroethylene mold containing solution E was immersed in liquid nitrogen for 30 min and then taken out.
[0089] (8) Place the polytetrafluoroethylene mold in a -16°C refrigerator and freeze for 5 hours.
[0090] (9) Take the polytetrafluoroethylene mold out of the refrigerator and place it in a room temperature environment to thaw for 10 hours.
[0091] (10) Repeat steps 9 and 10 for a total of 5 times.
[0092] (11) The sample is taken out of the mold to obtain the electronic skin.
[0093] (12) The electronic skin is encapsulated using the electronic encapsulant Ecoflex00-10, and the thickness of the encapsulation is 1 mm.
[0094] After testing, it was found that the electronic skin obtained in this comparative example had poor adhesion performance, could not be firmly adhered to the skin surface, and was easy to fall off.
[0095] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-adhesion anisotropic electronic skin, characterized in that: The composition of the raw materials according to mass percentage is: electronic skin surface patch 0.5wt%~3wt%, PVA 8wt%~25wt%, conductive antibacterial agent 1wt%~3wt%, water-retaining antifreeze agent 1wt%~3wt%, sodium tetraborate decahydrate 0.3wt%~1.5wt%, and the balance is deionized water.
2. The high-adhesion anisotropic electronic skin according to claim 1, characterized in that: The high-adhesion anisotropic electronic skin is prepared by mixing various raw materials evenly and pouring the mixture into a mold, and then using a cyclic freeze-thaw method.
3. The high-adhesion anisotropic electronic skin according to claim 1 or 2, characterized in that: The electronic skin surface patch is one of chitosan, carrageenan, curdlan gum, sodium alginate and hydroxycellulose.
4. The high-adhesion anisotropic electronic skin according to claim 1 or 2, characterized in that: The molecular weight of the PVA is 78,000 to 158,000.
5. The high-adhesion anisotropic electronic skin according to claim 1 or 2, characterized in that: The conductive antibacterial agent is one or both of silver nanowires and silver nanoparticles.
6. The high-adhesion anisotropic electronic skin according to claim 1 or 2, characterized in that: The water-retaining antifreeze agent is one of CaCl2 and polyol.
7. A method for preparing the high-adhesion anisotropic electronic skin according to any one of claims 1 to 6, characterized in that: The steps include: Step 1, adding the electronic skin surface patch to part of the deionized water, and mixing them evenly at 90-100° C. to obtain solution A; Step 2, adding PVA to solution A, mixing at 90-100° C. for 1.5-2 hours to obtain solution B; Step 3, adding the conductive antibacterial agent to solution B, and mixing uniformly by ultrasonication to obtain solution C; Step 4, adding the water-retaining antifreeze agent to the solution C, and mixing uniformly by ultrasonication to obtain a solution D; Step 5, adding sodium tetraborate decahydrate to the remaining deionized water, and mixing them uniformly at 90-100° C. to obtain solution E; Step 6, mixing solution D and solution E evenly to obtain solution F; Step 7, pouring solution F into a polytetrafluoroethylene mold with a thick copper block as the top cover; Step 8, immersing the bottom of the polytetrafluoroethylene mold containing solution F in liquid nitrogen for 20 to 40 minutes, and then taking it out; Step 9, placing the polytetrafluoroethylene mold in a refrigerator at -18 to -16°C and freezing for 5 to 8 hours; Step 10, taking the polytetrafluoroethylene mold out of the refrigerator, placing it in a room temperature environment, and thawing it for 10 to 15 hours; Step 11, repeat step 9 and step 10 3 to 5 times; Step 12, taking the sample out of the mold to obtain a highly adhesive anisotropic electronic skin; Step 13: Use an electronic encapsulation agent to encapsulate the obtained electronic skin.
8. The preparation method according to claim 7, characterized in that: In the solution D, the mass percentage of water is 72% to 85%.
9. The preparation method according to claim 7, characterized in that: The electronic encapsulant is one of Ecoflex00-10, Ecoflex00-20 and Ecoflex00-30.
10. The preparation method according to claim 7, characterized in that: The thickness of the encapsulant is 0.8-1.3 mm.